Pretreatment Thrombocytosis as a Prognostic Factor in Metastatic Breast Cancer - Athina Stravodimou; Ioannis A. Voutsadakis (International Journal of Breast Cancer)
Background. An elevated platelet count is often associated with malignancies, and it has been confirmed as an adverse prognostic factor in various cancers including early stage breast cancer. We sought to determine if thrombocytosis is also a prognostic factor in metastatic breast cancer. Patients and Methods. The records of 165 metastatic breast cancer patients with complete follow-up that had thrombocytosis or normal platelet counts were reviewed. Kaplan-Meier curves were constructed, and the survivals of the two groups were compared using the LogRank test. A Cox regression analysis was used to determine if thrombocytosis is an independent factor for overall and progression free survival. Results. There was a statistically significant difference in overall and progression free survival favoring the normal platelets group (LogRank test and 0.008, resp.). Thrombocytosis remained a significant adverse prognostic factor in multivariate analysis. Other independent prognostic factors for overall survival included age, ER/PR status, and grade. Conclusion. Thrombocytosis represents an independent adverse prognostic factor in patients with metastatic breast cancer. Thus metastatic breast cancer joins a range of cancers in which this easily measurable value can be used for clinical prognostication. Further use as a predictive value for specific treatments has a rationale and deserves to be investigated.